TROPHIC AND REPRODUCTIVE ECOLOGY OF A NEOTROPICAL CHARACID FISH HEMIBRYCON BREVISPINI (TELEOSTEI: CHARACIFORMES) (2014)
Hemibrycon brevispini is a Neotropical characid fish endemic in La Venada Creek, a headwater tributary of the Quindío River of Colombia (Cauca River drainage). It is mainly a diurnal insectivore with a diet dominated by benthic dipterans (Chironomidae, Simuliidae, Psychodidae, Culicidae, Calliphoridae, Dixidae and Muscidae), hymenopterans (Formicidae and Vespidae) and ephemeropterans (Baetidae), as well as allochthonous prey and items eaten accidentally. Microhabitats of mountain streams with lower water velocity tend to have more riparian vegetation and the associated terrestrial arthropods that are consumed by H. brevispini. It has three peaks in reproduction: December, April and August. Average fecundity was 776 mature oocytes per female.